Impact of radiotherapy on anorectal function in patients with rectal cancer following a watch and wait programme. (March 2019) - van der Sande, Marit E.; Hupkens, Britt J.P.; Berbée, Maaike; van Kuijk, Sander M.J.; Maas, Monique; Melenhorst, Jarno; Beets, Geerard L.; Breukink, Stéphanie O.
Highlights: Late dose-volume effects of radiotherapy on the anorectal function were studied in rectal cancer patients. 33.3% of the patients had major LARS (Low Anterior Resection Syndrome). Clustering and urge incontinence were the most common complaints. Trends towards higher Vaizey and LARS scores after higher doses to the anal sphincter complex were observed. Abstract: Background and purpose: To assess the long-term anorectal function in rectal cancer patients following a watch-and-wait policy after chemoradiotherapy and to investigate the dose–volume effects of radiotherapy on the anorectal function. Methods and materials: Thirty-three patients with primary rectal cancer who were treated with chemoradiotherapy and a watch-and-wait policy with minimum follow-up of 2 years were included. We assessed the anorectal function using anorectal manometry and patient reported outcomes (Vaizey and LARS score). Dose–volume histograms were calculated for the rectum and anal sphincter complex, and associations between the dose–volume parameters and anorectal function were assessed. Results: Dmean to the rectum and anal sphincter complex was 50.5 Gy and 44.7 Gy, respectively. After a median follow-up of 38 (range 23–116) months, 33.3% of the patients reported major LARS. Mean LARS score was 23.4 ± 11.3 and mean Vaizey score was 4.3 ± 4.1. The most frequent complaints were clustering of defaecation and faecal urgency. Trends towards a higher Vaizey and LARS score after higher anal sphincter complex dose were observed, although these associations were not statistically significant. Conclusions: This is the first study to investigate the late dose-volume effects of radiotherapy specifically on the anorectal function in rectal cancer patients. One-third of the patients had major LARS and the most frequent reported complaints were clustering and faecal urgency. Additionally, we observed trends towards worse long-term anorectal function after higher anal sphincter complex radiotherapy dose. However, this should be evaluated on a larger scale. Future efforts to minimise the dose to the sphincters could possibly reduce the impact of radiotherapy on the anorectal function.